EVALUATION OF THE EFFECTIVENESS OF THE MANAGEMENT OF ACCOUNTS RECEIVABLE - LYUDMILA MIKHAYLOVNA Kupriyanova; ALEXEY NIKOLAEVICH Boldyrev (Мир новой экономики, 2018)
The article is devoted to the problems of management of accounts receivable. In the daily activities of the traders come in different types of relations with legal entities and individuals, have entered into the transaction, carry out duties prescribed by law. As a result of the monetary obligations appear to be enforceable, and the obligations of the debtor in relation to the organization. In this regard, it is important to monitor performance, monitor debtors of receivables in order to minimize the risk of defaulting on debts. If you have overdue andpoor-quality receivables trade organization actually loses the ability to stabilize the financial situation. Provided effective Receivables Management based on control and monitoring, the possible solution to the major challenges to strengthen the financial condition of the organization. Such goals also requires the formation of a new type of management based on the highest level of professional competencies for effective management.